Clinical predictors of cardiac syncope at initial evaluation in patients referred urgently to a general hospital: the EGSYS score. Issue 12 (2nd June 2008) - Del Rosso, A; Ungar, A; Maggi, R; Giada, F; Petix, N R; De Santo, T; Menozzi, C; Brignole, M
Abstract : Objective: To develop, in patients referred for syncope to an emergency department (ED), a diagnostic score to identify those patients likely to have a cardiac cause. Design: Prospective cohort study. Setting: ED of 14 general hospitals. Patients: 516 consecutive patients with unexplained syncope. Interventions: Subjects underwent a diagnostic evaluation on adherence to Guidelines of the European Society of Cardiology. The clinical features of syncope were analysed using a standard 52-item form. In a validation cohort of 260 patients the predictive value of symptoms/signs was evaluated, a point score was developed and then validated in a cohort of 256 other patients. Main outcome measurements: Diagnosis of cardiac syncope, mortality. Results: Abnormal ECG and/or heart disease, palpitations before syncope, syncope during effort or in supine position, absence of autonomic prodromes and absence of predisposing and/or precipitating factors were found to be predictors of cardiac syncope. To each variable a score from +4 to –1 was assigned to the magnitude of regression coefficient. A score ⩾3 identified cardiac syncope with a sensitivity of 95%/92% and a specificity of 61%/69% in the derivation and validation cohorts, respectively. During follow-up (mean (SD) 614 (73) days) patients with score ⩾3 had a higher total mortality than patients with a score <3 both in the derivation (17% vs 3%; p<0.001) and in the validation cohort (21% vs 2%; p<0.001). Conclusions: A simple score derived from clinical history can be usefully employed for the triage and management of patients with syncope in an ED.